Adesão dos estados ao Pacto Nacional pelo Enfrentamento à Violência contra as Mulheres: desafios da institucionalização de políticas públicas de gênero nocontexto federativo brasileiro - Carolina Marra Sim?es Coelho (2015)
This research has the objective of analyzing the state governments adhesion process to National Pact for the Violence Confrontation against Women (2007). The creation of the Pact intended to establish national guidelines and incentivate states and cities to implement politics to confront the violence against women, which so far had been built under the exclusive dependence of the state governments and city initiatives, and it was done without a national coordination. From a gender perspective, Public politics are not neutral, specially when aimed to confront violence against women, hence the Pact is also affected by it. The states and cities adhesion process to the Pact was investigated through a theoric frame based on Federalism and its intergovernamental relations as much as on Feminist and Gender political theories, using quantitative and qualitative methods. It was, then, built a typology which let us stablish a scale of Institutionalization of the Pact from Poor (eight states), Medium (thirteen states) and Strong (six states). From there, we investigated the hipothesis, trying to identify which ones really helped the adhesion to and institutionalization of the Pact. Based on the result of modelling statistic regression, we could state that the adhesion to the Pact was helped by three factors: the number of active Women´sMovements in the state, the pre-existence of a State Council for the Women Rights and the fact that the state was or was not chosen by the SPM/PR as a priority for the adhesion. The hipothesis related to the Institutionalization rate that were confirmed were: the rape rate, the fiscal dependence of the state and the number of active Women´s Movements in the state. The qualitative data brought up other factors to the analisis, among them we highlight the political and partisan issue and the presence of Patriarchy in the political and social relations. We conclude that both Federalism and Gender are, in fact, central to understanding the adhesion process and institutionalization of the Pact by brasilian states.